Unveiling the multifaceted microbial strategies: Insights into ecological adaptations and interactions - Heng Chuan Law; Kathrie Rubil; Nur Iliyana Illang; Nazalan Najimudin; Mardani Abdul Halim (Malaysian Society for Microbiology, 2023)
Microorganisms, such as spanning bacteria, archaea and fungi, were ubiquitous and played pivotal roles in shaping ecosystems. This review offered a comprehensive investigation into the multifaceted strategies employed by microorganisms to thrive and adapt within complex ecological niches. Key themes explored in this review encompassed microbial defence mechanisms, biofilm formation, quorum sensing and altruistic behaviours. Microbial defence mechanisms were scrutinized, with a focus on bacteriocin production. Despite the costs associated with production, bacteriocins served as potent weapons that selectively targeted closely related strains, reducing competition and conferring indirect benefits to the producer's genetic kin. Biofilm formation, a critical facet of microbial survival, was discussed in detail. These structured microbial communities encased in self-secreted extracellular matrices provided structural support and protection, demonstrating their significance in diverse ecological contexts. The review further delved into the evolutionary implications of quorum sensing and altruism within microbial communities. Quorum sensing, a mechanism that allowed population density-dependent communication and cooperation, was revealed as essential for microbial survival. In conclusion, this review enhanced our understanding of the intricate strategies microorganisms employed for survival, adaptation and competition in intricate ecosystems. By shedding light on these mechanisms, it advanced our comprehension of microbial community dynamics and their indispensable roles in diverse environments.